KETIKA AYAT MENJADI HOOK: PENGARUH AYAT AL-QUR’AN DALAM VIDEO POLITIK TERHADAP KEPERCAYAAN PEMILIH MUDA - Rezal Ibrahim Hareka; Falizar Rivani; Rizki Dwi Febriansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The opening seconds of short political videos increasingly determine whether young users continue watching, while religious language may operate as a moral and identity cue. This study examines how Qur’anic verses used as an opening hook shape young voters’ trust in political communicators. An integrative literature review was conducted using 27 sources, comprising 26 peer-reviewed journal articles and one scholarly book. The literature was selected from studies on religious cues, digital religion, short-video politics, source credibility, misinformation, and youth political participation. The findings indicate that a Qur’anic hook can attract initial attention and strengthen perceived authenticity when the verse is contextually relevant, accurately presented, and consistent with the communicator’s conduct and policy message. The same device can reduce trust when audiences perceive sacred texts as decorative, manipulative, partisan, or disconnected from substantive political content. Its effect is therefore indirect and conditional. Attention is only an entry point, whereas trust develops through assessments of source credibility, message consistency, sincerity, and informational quality. Religiosity, political interest, media literacy, prior attitudes, and partisan congruence moderate these evaluations. The study proposes a conditional model and ethical guidelines for religiously framed political communication.